Analisis Kepuasan Masyarakat Terhadap Sistem Drainase - Anggerius Loi; Tafianus Hia; Andrew Christover Harefa; Serta Denius Daeli (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the level of community satisfaction with the drainage system in Gunungsitoli and to identify the factors influencing it. The research employs a quantitative approach with a descriptive method by distributing questionnaires to residents living in areas affected by the drainage system. Satisfaction measurement is conducted using a Likert scale based on five service quality dimensions: tangible, reliability, responsiveness, assurance, and empathy. The collected data are analyzed using descriptive statistics and the Community Satisfaction Index (CSI). The results indicate that the level of community satisfaction with the drainage system in Gunungsitoli falls into the moderately satisfied category. The assurance and tangible dimensions obtain relatively higher scores, while the reliability dimension is the lowest. The main problems identified include insufficient drainage capacity, poorly maintained drainage conditions, and blockages caused by waste. In addition, community participation is found to significantly influence the performance of the drainage system. The study concludes that improving community satisfaction with the drainage system requires an integrated approach combining technical improvements and increased public awareness. The local government needs to conduct routine maintenance, enhance drainage capacity, and promote community education on environmental cleanliness. This research is expected to serve as a reference for policy-making in more effective and sustainable urban drainage management.